Delayed conversion from central venous catheter to non‐catheter hemodialysis access associates with an increased risk of death: A retrospective cohort study based on data from a large dialysis provider. Issue 3 (5th March 2020) - Raimann, Jochen G.; Chu, Fang‐I; Kalloo, Sean; Zhang, Hanjie; Maddux, Frank; Wang, Yuedong; Kotanko, Peter
Abstract: Background: Hemodialysis initiation using a central venous catheter (CVC) poses an increased risk of death. Conversion to an arterio‐venous graft or fistula (AVF, AVG) improves outcomes. The relationship of primary dialysis access and timing of conversion from CVC to either AVF or AVG to all‐cause mortality was investigated. Methods: Two retrospective analyses in incident hemodialysis patients commencing treatment from January 2010 to December 2014 in dialysis clinics in the United States were conducted. Analysis 1 stratified as per access at initiation and those commencing with CVC were further stratified into (a) those that had a CVC, AVF, or AVG the entire year; (b) those that were converted to either AVF or AVG within either (i) the first or (ii) the second 6 months. Kaplan Meier analysis and Cox regression analysis were employed. Analysis 2 included all CVC patients investigating the relationship between access conversion time and mortality risk using a Cox proportional hazards model depicting the hazard ratio (HR) as a spline function over time. Results: Two subsets from initial 78, 871 patients were studied. In Analysis 1 both AVF (referent) and AVG [HR 1.12 (0.97 to 1.30)] associated with a better outcome than CVC [HR 1.55 (1.38 to 1.74)] during follow‐up. Lower mortality risk was seen for early switch from a CVC to AV access within the first 6 months [HR = 1.04 (0.97–1.13)] compared to a later switch [HR = 1.23 (1.10–1.38)]. Analysis 2 indicated that a CVC to AVF switch resulted in improved survival. Analysis 2 indicated early conversion to confer a survival benefit for CVC to AVG switch. Discussion and Conclusion: AVF and AVG show a survival benefit over CVC. Early conversion from CVC to either access improves survival. This emphasizes the importance of early preparation for dialysis by creation of an AVF or AVG and to convert CVCs early.